2021
DOI: 10.1039/d0ee03836a
|View full text |Cite
|
Sign up to set email alerts
|

Self-passivation of low-dimensional hybrid halide perovskites guided by structural characteristics and degradation kinetics

Abstract: The low-dimensional perovskite (LDP) holds great potential to deliver the highly stable and efficient solar cells. However, the fundamental understanding of the structure, composition and degradation mechanism of the LDP...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Notably, we found that the PbI 2 layers observed in the kink segment exhibit 6H lattice stacking (hexagonal, space group: R 3̅ m : H , a = b = 0.4557 nm, c = 2.0937 nm, α = β = 90°, γ = 120°), distinct from the 2H phase observed in the stem segment (Figure S1). Figure d displays a 6H PbI 2 atomic arrangement superimposed on the magnified HRTEM image, in which each trilayer is repeated at the third layer in the stacking sequence, together with the emergence of (101̅4) planes ( d spacing = 0.32 nm) , parallel to the TB and the broad sidewall facets (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, we found that the PbI 2 layers observed in the kink segment exhibit 6H lattice stacking (hexagonal, space group: R 3̅ m : H , a = b = 0.4557 nm, c = 2.0937 nm, α = β = 90°, γ = 120°), distinct from the 2H phase observed in the stem segment (Figure S1). Figure d displays a 6H PbI 2 atomic arrangement superimposed on the magnified HRTEM image, in which each trilayer is repeated at the third layer in the stacking sequence, together with the emergence of (101̅4) planes ( d spacing = 0.32 nm) , parallel to the TB and the broad sidewall facets (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Perovskite solar cells (PSCs) have attracted increased attention in recent years due to their high efficiency. [ 1–50 ] However, various instabilities under normal operating conditions (exposure to ambient air/moisture, illumination, elevated temperature, etc.) have been hindering the efforts in PSC commercialization.…”
Section: Introductionmentioning
confidence: 99%
“…14 Despite the importance of HP degradation reactions, a formal mechanism with rate orders and rate constants has not been reported. Some reports of effective rate constants and activation energies of perovskite degradation exist from fits to either inverse degradation times 30 or an Avrami model 31 based on the time-evolution of optical absorbance, 32 XRD patterns, [33][34][35][36] XPS peaks, 37 and AFM features of degrading HP films. 38 However, quantitative relationships between the rate of perovskite degradation and ambient partial pressure of oxygen, the illumination intensity, and the partial pressure of water vapor are still unknown.…”
Section: Introductionmentioning
confidence: 99%